Optimization of Gambier Industry Wastewater Treatment Plant (WWTP) Performance: a Systematic Approach for Environmental Sustainability - Desfitri, Erda Rahmilaila; Desmiarti, Reni; Permata, Adinda Ratu; Elizarni, Elizarni (Journal of Applied Agricultural Science and Technology, 2024)
The gambier industry in West Sumatra, particularly in Payakumbuh, is Indonesia's largest producer of gambier, contributing approximately 80-90% of the national production. This high production rate results in increased waste generated during the production process. This article discusses the potential environmental pollution from wastewater from the gambier industry and efforts to address this issue. The study notes that coagulation-flocculation and adsorption methods have efficiently treated textile industry wastewater. The study discusses the Wastewater Treatment Plant (WWTP) conditions in the gambier processing industry before optimization and the steps taken to improve its performance. Additionally, the study analyzes wastewater characteristics before and after treatment. The results of this study indicate that adding aerators and pH-adjusting agents to the WWTP can improve wastewater treatment performance, resulting in effluent that meets the quality standards set by government regulations. Moreover, treating wastewater with adding Poly Aluminium Chloride (PAC) reduces COD and BOD, indicating the degradation of organic components in gambier waste. COD removal efficiency is 92.65%, and BOD removal efficiency is 58.01%. This optimization results in an improved quality of gambier industry wastewater, reducing its negative environmental impact. These efforts are crucial to meet environmental regulatory standards established by the Indonesian government.